1997
DOI: 10.1209/epl/i1997-00431-5
|View full text |Cite
|
Sign up to set email alerts
|

Scaling exponents for turbulent velocity and temperature increments

Abstract: Measurements in a turbulent wake indicate that, in the inertial range, the power law exponents inferred from the transverse velocity and temperature increments are nearly equal and significantly smaller than the exponents of the longitudinal velocity increment. The relative magnitudes of the exponents for moments up to the eighth order have been determined using the extended self-similarity method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…Some groups have plotted v n r ∝ |v r | 3 ξ t n [9,12]. But more recently it has been argued that |v r | n ∝ |u r | 3 ξ t n (45) is theoretically more justified because Kolmogorov's 4/5-law gives an exact prediction for the longitudinal third-order structure function and therefore |u r | 3 is a good point of [16,22,31,59,60].…”
Section: Appendix A: Extended Self-similaritymentioning
confidence: 99%
“…Some groups have plotted v n r ∝ |v r | 3 ξ t n [9,12]. But more recently it has been argued that |v r | n ∝ |u r | 3 ξ t n (45) is theoretically more justified because Kolmogorov's 4/5-law gives an exact prediction for the longitudinal third-order structure function and therefore |u r | 3 is a good point of [16,22,31,59,60].…”
Section: Appendix A: Extended Self-similaritymentioning
confidence: 99%
“…In [8,38,39] the authors plot v n against |u 3 | and obtain that the transverse exponents is smaller than the longitudinal one, ξ n t < ξ n l . In Fig.…”
mentioning
confidence: 99%
“…Pioneering (Siggia 1981;Kerr 1985) as well as more recent (Kestener and Arneodo 2003;Kestener 2003;Chen et al 1997a) numerical DNS studies have shown that the enstrophy field is more intermittent than the dissipation field. As suggested by Chen et al (1997b), this difference is likely to result from the difference observed in the scaling exponents f p L and f p T of longitudinal and transverse velocity structure functions, respectively (Malécot et al 2000;Van de Water and Herweijer 1996;Camussi and Benzi 1997;Boratov and Pelz 1997;Grossmann et al 1997;Antonia and Pearson 1997;Dhruva et al 1997). More precisely, Chen et al (1997b) reported numerical results that demonstrate the possible validity of a different RSH for the transverse direction (RSHT) that connects the statistics of the transverse velocity increments to the locally averaged enstrophy in the inertial range.…”
Section: Discussionmentioning
confidence: 98%
“…Actually this estimate is comparable but still slightly larger than the value C 2 . 0.04 extracted from the experimental analysis of transverse velocity increments (Malécot et al 2000;Van de Water and Herweijer 1996;Camussi and Benzi 1997;Boratov and Pelz 1997;Grossmann et al 1997;Antonia and Pearson 1997;Dhruva et al 1997;Chen et al 1997b). Even though one has to be cautious as regard to the rather modest value of R k = 140 of the analyzed DNS data, it is not so surprising that when investigating the full 3D fluctuations of the velocity field, one realizes that this field is much more intermittent than previously estimated from the fluctuations of one of its component only.…”
Section: Velocity Fieldmentioning
confidence: 99%